Relationship between collagen disorders and hidradenitis suppurativa regarding two cases of Loeys-Dietz syndrome. - Vultaggio, M.; Diluvio, L.; Artosi, F.; Cannizzaro, M.V.; Bertoldo, F.; Ruvolo, G.; Campione, E.; Bianchi, L. (European Journal of Pediatric Dermatology, 2023)
Loeys-Dietz syndrome (LDs) is an inherited disorder characterized by connective tissue changes similar to those that occur in Ehlers-Danlos and Marfan syndrome. The authors describe two new cases of this syndrome, noting among the cutaneous signs the presence of hidradenitis suppurativa (HS) localized also in atypical sites. Since a higher incidence of HS has been reported in other diseases characterized by collagen disorders, such as Ehler-Danlos syndrome, Marfan syndrome, autoimmune spondyloarthropathies, lichen sclerosus, dyselastic striae, the authors discuss the significance of such alterations in the pathogenesis of HS.